IoT based SMART FARMING SYSTEM - M.V.Prabhakaran, Kavitha.G, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Internet of Things (IoT) technology has brought revolution to each and every field of common man’slife by making everything smart and intelligent. IoT refers to a network of things which make a self-configuring network. The development of Intelligent Smart Farming IoT based devices is day by dayturning the face of agriculture production by not only enhancing it but also making it cost-effectiveand reducing wastage. The aim/objective of this report is to propose IoT based Smart FarmingSystem assisting farmers in getting Live Data (Temperature, Soil Moisture) for efficient environmentmonitoring which will enable them to increase their overall yield and quality of products. The IoTbased Smart Farming System being proposed via this report is integrated with ArduinoTechnologymixed with different Sensors and a Wifi module producing live data feed that can be obtained onlinefrom Thingsspeak.com. The product being proposed is tested on Live Agriculture Fields giving highaccuracyover98%in datafeeds